A Feminist Stylistic and Affective Analysis of Melancholy and Memory in Lang Leav’s Revelation - Intan Maulina; Saiful Anwar Matondang; M Manugeren; Zayed Hussein Saleh Al-Mudhafar (Universitas Islam Negeri Palopo, 2025)
This study examines the linguistic construction of melancholy and memory in Lang Leav’s poem “Revelation” from Memories (2015) through an integrated framework of feminist stylistics and affect theory. While contemporary feminist scholarship has increasingly engaged with affect, limited attention has been given to how linguistic form in minimalist poetry structures emotional knowledge. Addressing this gap, the study adopts a qualitative interpretive-analytical approach, combining close stylistic analysis with affective interpretation. Drawing on feminist stylistics (Mills, 1995; Montoro, 2023) and affect theory (Ahmed, 2014; Hemmings, 2024), the analysis focuses on lexical choice, grammatical patterns, and figurative language to examine how emotion operates as a mode of knowing. The findings demonstrate that Leav’s minimalist diction and syntactic restraint construct melancholy not as emotional passivity but as an epistemic process of self-recognition. Memory functions as an affective medium through which feminine subjectivity negotiates identity and emotional continuity. The study conceptualizes this strategy as affective minimalism: a poetic mode in which linguistic economy intensifies emotional cognition rather than diminishing it. This challenges traditional binaries between emotion and reason; positioning affects as a legitimate epistemological resource. Theoretically, the study extends feminist stylistics toward affective epistemology and contributes to contemporary feminist poetics by showing how minimalist poetic language can articulate emotional agency and feminist self-representation in the digital age.